Efektivitas Pendekatan Hipnosis dalam Pembelajaran Apresiasi Seni Rupa - Hasnawati, Hasnawati; Sultan, Sudirman (Universitas Negeri Makassar, 2016)
This research aimed to describe the effectiveness of hypnosis approach in learning appreciation applied art based on local culture at the seventh grade in 4 State Junior High School Pallangga. This research was descriptive research. The population of this research was all the seventh grade students in 4 State Junior High School Pallangga consisting of 5 classes. The samples of this research were 2 classes with 42 students, 22 students from class VII 3 and 20 students from class VII 4. The data collection was done by doing test, observation, interview and documentation. The instruments of the data collection were multiple choices, observation guidance, interview protocol and camera. The data analysis was descriptive qualitative. The result of the research showed that the application of hypnosis was effective applied in learning appreciation applied art based on local culture at the seventh grade in 4 State Junior High School Pallangga Gowa Regency